Understanding facilitators and barriers to adherence in home-based pulmonary rehabilitation for chronic obstructive pulmonary disease patients using the Health Belief Model: a qualitative study - Zeng, Qiuxuan; Chen, Wenli; Xu, Siyi; Yang, Xu; Xue, Dandan; Peng, Yuhang; Lin, Xiaohong; Yu, Yingwen; Huang, Huixin; Huang, Ping; Dong, Min; Li, Jiaying (Frontiers in Public Health, 2025)
BackgroundHome-based pulmonary rehabilitation (PR) is a key non-pharmacological intervention for chronic obstructive pulmonary disease (COPD), but poor adherence limits its effectiveness. The factors influencing adherence, particularly from the patients’ perspective, are not well understood. This study aims to identify the factors that promote or hinder adherence to home-based rehabilitation in COPD patients, to inform more effective and personalized strategies.MethodsThis study guided by Health Belief Model (HBM), and data were collected through semi-structured in-depth interviews with eligible COPD patients during May and July 2024. Deductive thematic analysis approach was used to analyze the data.ResultsEighteen patients were recruited through purposive sampling. Two main themes emerged-facilitating health beliefs and challenges- along with five subthemes under the HBM framework: perceived threats, perceived benefits, cues to action, self-efficacy, and perceived barriers. In total, 28 categories were identified (21 facilitators, 7 barriers), including 11 newly discovered facilitators and one new barrier. Newly identified facilitators included physical limitations and fatigue, emotional distress, perceived ineffectiveness, time constraints, caregiving responsibilities, lack of support, cost, poor exercise conditions, reduced medical dependence, self-awareness of functional decline, attention-seeking behaviors, environmental cues, mental resilience, and religious beliefs. The new barrier related to environmental limitations and poor exercise conditions.ConclusionThis study underscores facilitators and barriers influencing home-based PR adherence within the HBM framework. Facilitators include broad factors related to perceived benefits, cues to action, self-efficacy, and perceived threats, while barriers encompass physical limitations, time constraints, and insufficient support. Flexible, personalized programs and greater family involvement can enhance adherence, improve long-term outcomes, and mitigate the rising burden of chronic diseases in aging societies.